Developing a team mission statement: Who are we? Where are we going? How are we going to get there? - Martin, Eric M.; Cowburn, Ian; Mac Intosh, Andrew (Journal of sport psychology in action, 2017)
A mission statement defines a group's purpose, describes the beliefs in how a group should function, and indicates the unique values of a group. Few studies in sport have specifically investigated the influence of a mission statement, but several high-performance teams have cited mission statements as a key for improved team performance and functioning. Recently, it has become more common for consultants to provide overviews of team building interventions in sport. However, even with initial evidence that mission statements may be beneficial for team cohesion and performance, little has been written about the process of developing a mission statement in the sporting realm. Therefore, the purpose of the article is to outline the authors' experiences leading an activity to develop a season-long mission statement with a collegiate varsity gymnastics team. Additionally, an overview of how the consultants gained entry and developed trust with the coaching staff and team, as well as reflections on what went well in the process and what could be enhanced for the greatest impact are discussed.